CD-19-directed immunotherapy resistance mechanisms of B-precursor acute lymphoblastic leukemia - E. V. Glukhanyuk; A. V. Stepanov; A. M. Popov; M. A. Maschan (Онкогематология, 2019)
Immunotherapy is the most rapidly evolving field in clinical malignant hematology. Targeting of the B-lineage surface antigen CD19 in B-lineage acute lymphoblastic leukemia and B-cell lymphoma is a story of great success. Recently two approaches of CD19 immunotargeting were approved for clinical application: CD3 × CD19 bi-specific T-cell engager blinatumomab and CD19 chimeric antigen receptor (CAR) Tcells. Both approaches demonstrated an unprecedented activity in a cohort of patients with relapsed and refractory B-cell leukemia and lymphoma both in the adult and pediatric population. Early clinical research has showed that tumors are able to escape the immunological control and become resistant to the immune attack. Mechanisms of the tumor immune escape are being actively studied and include diverse pathways, such as alternative splicing of CD19 and immunosuppressive tumor microenvironment. Current review briefly summarizes data regarding the mechanisms of CD19-positive leukemia resistance to CD19 immune targeting and discusses potential approaches to overcome it.